Telomere length is highly inherited and associated with hyperactivity-impulsivity in children with attention deficit/hyperactivity disorder - Costa, Danielle de Souza; Rosa, Daniela Valadão Freitas; Barros, Alexandre Guimarães Almeida; Romano-Silva, Marco Aurélio; Malloy-Diniz, Leandro Fernandes; Mattos, Paulo; de Miranda, Débora Marques (Frontiers in Molecular Neuroscience, 2015)
Telomere length (TL) is highly heritable, and a shorter telomere at birth may increase the risk of age-related problems. Telomere length (TL) is highly heritable, and a shorter telomere at birth may increase the risk of age-related problems. Additionally, a shorter TL may represent a biomarker of chronic stress and has been associated with psychiatric disorders. However, no study has explored whether there is an association between TL and the symptoms of one of the most common neurodevelopmental disorders in childhood: Attention Deficit/Hyperactive Disorder (ADHD). We evaluated 61 (range, 6-16 years) ADHD children and their parents between 2012 and 2014. Telomere length was measured with a quantitative polymerase chain reaction method with telomere signal normalized to the signal from a single copy gene (36B4) to generate a T/S ratio. Family data was processed through a GEE model to determine the effect of parental TL on children TL. Inattentive and hyperactive-impulsive symptoms were also evaluated in relation to TL. For the first time, we found general heritability to be the major mechanism explaining interindividual telomere length variation in ADHD (father-child: 95%CI=0.35/0.91, p<0.001; mother-child: 95%CI=0.38/0.74, p<0.001). The hyperactive-impulsive dimension of ADHD was related with children’s TL (r=-339, p=0.008) and maternal TL (r=-264, p=0.047), but not with paternal TL (p>0.05). The ADHD inattentive dimension was not significant associated with TL in this study (p>0.05). TL was shown to be a potential biomarker of the ADHD symptoms burden in families affected by this neurodevelopmental disorder. However, it is crucial that future studies investigating the rate of telomere attrition in relation to psychiatric problems to consider the strong determination of telomere length at birth by inheritance.